Study of Some Optical Properties of Poly Methylmethacrylate Copper Nanocomposites Films - Nahida B. Hasan (Journal of Global Pharma Technology, 2016)
The addition effect of nano Cu on some optical properties for poly methyl-methacrylate has been investigated. Poly methyl-methacrylate with different weight percentages of nano Cu content and different thickness have been prepared. The wavelength range for which absorption spectra have been recorded is (200-800) nm. For indirect allowed and forbidden transition the absorption coefficient, extinction coefficient and energy gap have been determined. Results show an increasing in absorption coefficient and extinction coefficient and decreasing in the energy gap with the Wt.% concentration of nano Copper. Scanning Electron Microscope (SEM) Measurements certificates the compatibility between various components of the polymers and nano materials through the detection of phase separations and interfaces. All figures show the very detailed three-dimensional images at very high magnifications for all films.Keywords: Polymethyl-methacrylate, Nanoparticles, Nano-composites.